Changes in the Concept of Lithuanian Identity in Public Consciousness in 2008–2017 - Savicka, Aida (Sociologija. Mintis ir veiksmas, 2019)
What is the prevailing concept of Lithuanian identity and the importance of different criteria used to define it? How do they fit in with the newly constructed European identity? Based on the data of the European Values Survey, the article analyzes the dominant notion of Lithuanian identity in our society, the importance of criteria used to define it, and the dynamics of evaluations of the importance of these criteria in the period from 2008 to 2017, revealing essential sociodemographic and other differentiation factors. The problem of the complex interrelationship between a Lithuanian and European identity is also examined, denying the myths of their inevitable contradiction.